Relation between frontal plane center of mass position stability and foot elevation during obstacle crossing. (12th February 2021) - Yamagata, Momoko; Tateuchi, Hiroshige; Pataky, Todd; Shimizu, Itsuroh; Ichihashi, Noriaki
Abstract: High foot elevation during obstacle crossing is viewed as a conservative strategy in older adults, but excessive foot elevation may result in large mediolateral center of mass (CoM) displacement. Since an incorrect transfer of CoM can lead to balance loss during locomotion, both appropriate foot elevation and CoM position must be controlled and coordinated by adjusting body segment positions. However, no studies have revealed time profiles of CoM position by coordinated segment movements and the relation of foot elevation with CoM position during obstacle crossing. Twenty-five healthy older adults crossed an obstacle (depth: 1 cm, width: 60 cm, height: 8 cm) during comfortable-speed walking. Synergy indices were calculated during lead- and trail-limb swing using uncontrolled manifold analysis. High synergy index values indicate a strong multi-joint kinematic synergy, or co-fluctuations in segment movements, to control CoM position. The maximum foot heights of the swing limbs were calculated as the maximum vertical distance between the most distal foot point and the ground. In the mediolateral direction, synergy index values during early lead-limb swing were significantly greater than during early trail-limb swing, and in the vertical direction, large synergy index values were found during early- and mid-swing phases. Moreover, maximum trail-foot height was correlated to vertical synergy index during early phase. CoM position was not well controlled by a kinematic synergy during trail-limb swing and the low control of CoM position was observed with great trail-foot height. The results suggest that a conservative strategy with great trail-foot height would not always be helpful for successful obstacle crossing.